Opsi Perbaikan Tanah berdasarkan Kondisi Tanah (Studi Kasus di Cibitung, Bekasi - Agrina, Dwi (JOURNAL INFORMATION TECHNOLOGY ENGINEERING AND SCIENCE, 2024)
Soft soil problems are common in Indonesia. This study is based on a case study of soft soil problems in Cibitung, Bekasi. The determination of treatment to improve the soil needs to be done based on field data results. Determination of repair options includes the type of construction, soil type conditions, time, cost and feasibility of a method. Based on soil conditions with a soft soil thickness more than 2m, need such as PVD or slab on pile treatment. If it is less than 2m, soil mixing or replacement can be option.